Representation of Gender Equality in the “Barbie” Film: Semiotic Analysis of Roland Barthes - Dewayani, Ardya; Azwar (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
This research focuses on the representation of gender equality in the live-action film "Barbie" produced by Warner Bros. which was released in 2023 and directed by Greta Gerwig. This film illustrates how the characters Barbie and Ken face differences in the social construction of gender between the utopian world they live in and the real world. Gender equality itself is the assumption that men and women have the same position. Through nurture theory, we can assume that gender is a characteristic inherent in men and women through social construction, not due to biological factors. This research uses qualitative methods by collecting data through documentary, observational, and literature methods. The data was then analyzed using Roland Barthes' semiotics. In this film, we see how female characters have positions of power in government against stereotypes, dare to defend themselves when they are ridiculed as a form of resistance to objectification, women who then dare to express their opinions against marginalization, and male characters who dare to be vulnerable in their actions. express their feelings so that there is no more emotional suppression. These four phenomena are indicators that serve as an assessment of the analysis of gender equality in this research. Thus, through the film "Barbie" it is known that there are four research units that represent stereotypes, objectification, marginalization, and emotional oppression.